Integrating Dilemma Stories into Chemistry Learning: Analyzing Students’ Critical Thinking Skills - Hadinugrahaningsih, Tritiyatma; Rahmawati, Yuli; Syaadah, Rika Siti; Dewi, Fitri Sumalia; Az-Zahra, Shakira; Tamarani, Fitri (Jurnal Tadris Kimiya, 2024)
Critical thinking is a key competency for 21st-century students, essential for logical reasoning, decision-making, and academic success. However, studies indicate that Indonesian students often exhibit low levels of critical thinking. Chemistry, particularly topics like oxidation-reduction reactions, offers real-life applications, such as waste oil disposal, that can be leveraged to improve these skills. This study aims to analyze the effectiveness of integrating dilemma stories into project-based learning (PBL) to enhance students' critical thinking skills in the context of oxidation-reduction reactions. The study was conducted at SMAN 77 Jakarta with 36 students from Class X Mathematics and Natural Science 2. A qualitative approach was used, with data collected through observations, reflective journals, interviews, and critical thinking tests. The integration of dilemma stories in PBL was implemented through five stages: value reflection, problem-solving, project development, monitoring and evaluation, and transformation. The findings indicate significant improvements in students' critical thinking, creativity, collaboration, and problem-solving skills. Based on test results, students achieved level 3 (Acceptable) in critical thinking. The approach also enhanced their understanding of chemical concepts and awareness of addressing real-world problems. The integration of dilemma stories within PBL has proven effective in fostering critical thinking and other 21st-century skills in chemistry learning. This approach can serve as a model for innovative educational practices in STEM subjects.